EXISTENCE OF LEARNING TAHFIDZ AL-QURAN IN MADRASAH ALIYAH ISLAMIC CENTER OF NORTH SUMATERA - Achyar Zein, Ali Imran Sinaga, Marni Agustia (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: The purpose of this study was to determine, 1) the existence of Al Quran learning in the NorthSumatra Islamic School, 2) the structure of the Al Quran learning curriculum in the Islamic School inNorth Sumatra. The approach used is a qualitative field (field research). Qualitative research is used todescribe words and actions to understand phenomena experienced by natural research objects or in thecontext of wholeness, in this research, the instrument is the learning of the Koran, so the type of researchused is qualitative with a phenomenological approach. The findings of this study are 1) The ability of theNorth Sumatra Islamic Center Madrasah Aliyah in maintaining its existence both within the IslamicCenter North Sumatra Foundation and its surrounding environment can already be proven by themadrasa. 2) In the learning process, teachers who teach at the North Sumatra Islamic Center only usethe method they got from their previous tahfizhul Quran teachers without knowing the name of themethod. But it does not reduce the ability of teachers and the quality of students in teaching. 3) Teachingmaterials are only intended for class X students. 4) The strategy used by the North Sumatra IslamicCenter Madrasah Aliyah in maximizing the learning of Tahfiz Alquran, namely: Reducing the number ofstudents in the tahfizh class which initially numbered from 20 to 25 people. Changes in memorizationtime which were initially implemented in the morning and evening, are combined into the morningbefore formal study hours. A tahsin program was formed for new students. Do not classify studentsbased on their speed in memorization. 5) Evaluation is carried out several times a year, namely dailyevaluation, evaluation of the increase in the Quran, semester evaluation and annual evaluation.